Creutzfeldt-Jakob disease and lyophilised dura mater grafts: report of two cases. - Esmonde, T (1993)
Two further cases of Creutzfeldt-Jakob disease (CJD) in association with cadaveric dura mater grafts are described. The clinical features of all such reported cases resemble more closely those of sporadic CJD, in contrast with kuru and the cases of CJD which have arisen after therapy with human pituitary-derived growth hormone. This observation may reflect the route of inoculation of the agent.